PP.42.10: THE RELATIONSHIP BETWEEN BLOOD PRESSURE AND BCLL POLYMORPHISM OF THE GLUCOCORTICOID RECEPTOR GENE IN PATIENTS TREATED BY GLUCOCORTICOIDS. (June 2015) - Ciric, J.; Beleslin, B.; Antic, I.; Lalic, T.; Stojanovic, M.; Stojkovic, M.; Nisic, T.; Savic, S.; Damjanovic, S.; Zarkovic, M.
Abstract : Objective: Certain Bcll glucocorticoid receptor gene polymorphism is found to be linked with tissue specific glucocorticoid sensitivity and associated with metabolic syndrome. The aim of this study was to evaluate association of Bcll polymorphism with the occurrence of side effects of the treatment with intravenous methylprednisolone (iv MP) in patients with Graves' orbitopathy (GO). Glucocorticoids (GC) are used in the treatment of a broad (wide) spectrum of diseases in the dosage and duration (of) which often leads to moderate to severe complications. Although there are frequent side effects, weight gain, hypertension, dyslipidemia, impaired glycemic control parameters are not predictably present. Design and method: The study group included 22 subjects (17 female and 5 male) treated with two doses of 500 mg iv MP during three days, followed by oral prednisone 40 mg/d tapered to 10 mg/d during four weeks. Six courses of therapy were performed. Results: Nine patients had no glucocorticoid gene receptor polymorphism, 11 were heterozygous for Bcll and 2 patients were homozygous. All patients had a good response to the treatment of GO. Homozygous patients were slightly overweight with normal metabolic profile, but during the treatment cholesterol and blood pressure increased. They also tended to develop hypokalemia. Three of nine patients (1 obese, 2 overweight, 6 with normal weight) with no polymorphism had glucose intolerance, mild arterial hypertension and increased cholesterol before the treatment and they were stable during the treatment. Moderate hypertension in two subjects were also stable with no additional therapy. Four of eleven heterozygous patients (2 obese, 2 overweight, 7 with normal weight) had glucose intolerance and increased cholesterol, but during the treatment they normalized metabolic profiles by balanced nutrition. Two of three patients with well controlled moderate hypertension observed worsening of blood pressure. Conclusions: In conclusion, there was no significant difference in distribution of arterial hypertension before the treatment by glucocorticoids between groups with and without Bcll polymorphism. In this small group of patients Bcll polymorphism was not useful in prediction of blood pressure or other metabolic parameters response during the treatment.